Online measurement of dissolved carbon monoxide concentrations reveals critical operating conditions in gas fermentation experiments. Issue 1 (1st October 2020) - Mann, Marcel; Miebach, Katharina; Büchs, Jochen
Abstract: Syngas fermentation is one possible contributor to the reduction of greenhouse gas emissions. The conversion of industrial waste gas streams containing CO or H2, which are usually combusted, directly reduces the emission of CO2 into the atmosphere. Additionally, other carbon‐containing waste streams can be gasified, making them accessible for microbial conversion into platform chemicals. However, there is still a lack of detailed process understanding, as online monitoring of dissolved gas concentrations is currently not possible. Several studies have demonstrated growth inhibition of Clostridium ljungdahlii at high CO concentrations in the headspace. However, growth is not inhibited by the CO concentration in the headspace, but by the dissolved carbon monoxide tension (DCOT). The DCOT depends on the CO concentration in the headspace, CO transfer rate, and biomass concentration. Hence, the measurement of the DCOT is a superior method to investigate the toxic effects of CO on microbial fermentation. Since CO is a component of syngas, a detailed understanding is crucial. In this study, a newly developed measurement setup is presented that allows sterile online measurement of the DCOT. In an abiotic experiment, the functionality of the measurement principle was demonstrated for various CO concentrations in the gas supply (0%–40%) and various agitation rates (300–1100 min −1 ). In continuous stirred tank reactor fermentation experiments, the measurement showed reliable results. The production of ethanol and 2, 3‐butanediol increased with increasing DCOT. Moreover, a critical DCOT was identified, leading to the inhibition of the culture. Thus, the reported online measurement method is beneficial for process understanding. In future processes, it can be used for closed‐loop fermentation control. Abstract : A new, non‐invasive technique for determining the dissolved carbon monoxide tension (DCOT) in stirred tank reactors is presented. The technical concept and application of the online measurement technique in anaerobic fermentations using the model acetogen Clostridium ljungdahlii is reported. A critical dissolved carbon monoxide tension (DCOTcrit), which leads to a metabolic collapse of continuous fermentations, is detected even before changes become apparent in the exhaust gas analysis.